La agresividad en el desarrollo integral de los niños y niñas de primer grado de la unidad educativa Juan Lavalle, provincia de Chimborazo período 2015-2016 - Carrillo Romero, Janeth Soledad (2017)
This research is aimed at determine how is associated the violent behavior o in the Integral Development of children from the first grade of the educational Unit Juan Lavelle, province of Chimborazo period 2015-2016. With a population of 8 girls and 17 boy with a total of 25 first grade children of basic Education. The method used was inductive and deductive the research design is not. experimental, because in the investigative process it was not manipulated, any analytical since the features of the reality found are identified before the phenomenon investigated and seeking the problem explanations, causes and effects . Ii is because the information is taken from the involved elements where the problem occurs, the design type is descriptive since it will help to describe the two variable, the technique used is the observation because it captures the object investigated in a straight line, using the observation data sheet as the instrument that allowed the analysis and interpretation of results, concluding that there are activities to decrease aggressiveness, levels, that will help to enhance different skills that contribute to the comprehensive development to children.